Drug Utilization Study of Drugs of Complementary and Alternative System of Medicine in Patients with Chronic Painful Musculo-Skeletal Conditions - Vikas Dhikav; Sonia Mor; Wasifa Muzaffar; Nidhi Agarwal; Sheikh Raisuddin; Kuljeet Singh Anand (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2016)
Background: Use of drugs of Complementary & Alternative System of Medicine (CAM) is believed to be common. However, data on its prevalence is not known. Similarly, in patients with chronic diseases (e.g. chronic pain), there is no information about its usage. Additionally, it is believed that those who are not being relieved/satisfied with drugs of mainstream medicine usually use drugs of CAM. Objective: We wanted to know the prevalence and predictors of use of drugs of CAM in patients with chronic painful musculo-skeletal conditions. Also, an attempt was made to know that those with higher pain scores were more likely to use CAM or not. Methods: Patients coming to Outpatient Department of Pain Clinic were recruited for the present study. A pre-designed proforma was administered to all participants and study objectives were explained. All the patients gave their written and informed consent for enrolment in the study. Results: A total of 60 patients (M:F=30:30; mean age±SD=48.22±14.33 years) were recruited for the present study. The diagnosis of the patient was as follows (Neuropathy=20, Low back ache=17, cervical spondylitis=6, headache=4, mid back pain=4, osteoarthritis=4, frozen shoulder=3, Rheumatoid arthritis=2). Out of the study sample (n=60), a total of 16 patients used drugs of CAM (26.6%). A total of 9 patients used drugs with main stream medications (56.4%), signifying majority of CAM users used them with mainstream medications. Most common reasons of use of CAM were safety (less common side effects) and perceived benefits. None of the patient informed their physicians about the use of drugs of concomitant CAM usage. A total of 20 patients had neuropathy (diabetic neuropathy), and the frequency of usage of those with diabetic and non-diabetic neuropathy was same (Chi-Square test of proportion p-value>0.05). Also, those who used CAM and had higher pain scores did not have a significant difference with those who had a relatively lower pain scores (Chi-Square test of proportion p-value>0.05). The same was confirmed using linear regression model (R2=0.03). This implied that those with higher pain scores are as likely to use CAM compared to those with relatively lower pain scores. None of the patient reported any ADR with the use of drugs of CAM in the present study. Conclusions: Use of drugs of Complementary & alternative system of medicine is very common in patients with chronic painful musculo-skeletal conditions. Also, those with higher pain scores are as likely to use drugs of CAM compared to those with lower scores implying other factors play role in taking up the choice to use CAM.